ByzRev 07.2025.039: Susana Torres Prieto, The Early Slavs: The First Centuries of Eastern Europe: (Routledge Studies in the History of Russia and Eastern Europe). London – New York: Routledge 2025. - Curta, Florin (The Byzantine Review, 2025)
Susana Torres Prieto, The Early Slavs: The First Centuries of Eastern Europe (Routledge Studies in the History of Russia and Eastern Europe). London – New York: Routledge 2025. 211 pp. – ISBN 978-1-032-25113-4